The Campsicnemus popeye species group (Diptera: Dolichopodidae) from French Polynesia - Evenhuis, Neal L. (Zootaxa, 2013)
A new species-group (the popeye group) of the mega-diverse dolichopodid genus Campsicnemus from French Polynesia is described to include six new species: C. craigi Evenhuis, sp. nov.; C. elinae Evenhuis, sp. nov.; C. meyeri Evenhuis, sp. nov.; C. moorea Evenhuis, sp. nov.; C. pectinatus Evenhuis, sp. nov.; and C. popeye Evenhuis, sp. nov. Keys to Campsicnemus species groups in French Polynesia and to species in the C. popeye group are given.